Analisis Peningkatan Kinerja Pegawai Melalui Pengembangan Karir, Kompensasi, dan Motivasi - Vanisa Artha Ayuwangi; Muhammad Tahwin (eCo-Fin, 2025)
A government agency's HR department plays a crucial role in accomplishing its goals and objectives. Career growth, pay, and motivation are all ways to improve employee performance. This study aims to ascertain how employee performance is affected by career growth, pay, and motivation. This study was carried out at the Rembang Regency Regional Personnel Agency, which employs 48 people. Every member of the population was used in the sampling process (saturated sample). Multiple linear regression analysis was used to handle and examine the acquired data. According to the study's findings, performance is positively impacted by motivational factors but is negligibly impacted by career development and remuneration factors. Only 63.3% of the performance variable can be explained by this research model; the remaining portion is due to additional factors that are not covered in this model. These findings provide attention for related parties in terms of management to integrate career development programs with work-based compensation programs to create a reward system that can encourage performance results.